Activating β‐catenin signaling in CD133‐positive dermal papilla cells increases hair inductivity. (11th July 2016) - Zhou, Linli; Yang, Kun; Xu, Mingang; Andl, Thomas; Millar, Sarah E.; Boyce, Steven; Zhang, Yuhang
Abstract : Bioengineering hair follicles using cells isolated from human tissue remains a difficult task. Dermal papilla (DP) cells are known to guide the growth and cycling activities of hair follicles by interacting with keratinocytes. However, DP cells quickly lose their inductivity during in vitro passaging. Rodent DP cell cultures need external addition of growth factors, including WNT and BMP molecules, to maintain the hair inductive property. CD133 is expressed by a subpopulation of DP cells that are capable of inducing hair follicle formation in vivo . We report here that expression of a stabilized form of β‐catenin promoted clonal growth of CD133‐positive (CD133+) DP cells in in vitro three‐dimensional hydrogel culture while maintaining expression of DP markers, including alkaline phosphatase (AP), CD133, and integrin α8. After a 2‐week in vitro culture, cultured CD133+ DP cells with up‐regulated β‐catenin activity led to an accelerated in vivo hair growth in reconstituted skin compared to control cells. Further analysis showed that matrix cell proliferation and differentiation were significantly promoted in hair follicles when β‐catenin signaling was up‐regulated in CD133+ DP cells. Our data highlight an important role for β‐catenin signaling in promoting the inductive capability of CD133+ DP cells for in vitro expansion and in vivo hair follicle regeneration, which could potentially be applied to cultured human DP cells. Abstract : We engineered a triple transgenic mouse model to express a stabilized ΔN‐β‐catenin in CD133+ DP cells. Here we show that up‐regulation of β‐catenin signaling not only enhances the abilities of CD133+ DP cells to expand in vitro but also leads to an accelerated in vivo hair growth in reconstituted skin, which could potentially be applied to cultured human DP cells.